2009
DOI: 10.1002/car.1057
|View full text |Cite
|
Sign up to set email alerts
|

Report on the implementation and evaluation of an interprofessional learning programme for inter‐agency child protection teams

Abstract: Effective collaborative working between the different professions and agencies working to safeguard children is essential. Lack of knowledge of others' roles, perceived differences in status and expertise, and negative stereotypes are examples of why this can be difficult to achieve. A facilitated interprofessional learning (IPL) programme was implemented to assess if such an intervention could overcome some of the barriers to effective interprofessional and inter-agency team working. Six teams based in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Fourth, the perceived problems of professional tribalism, status/power differentials and resource shunting, identified in Table 3, are consistent with those identified as barriers to collaboration in other studies (see Rummery and Glendinning 1997). It was found that considerable time was needed to address these issues and explore ways that such cultural differences could be mitigated, a finding consistent with a recent study of an inter-professional learning programme in child protection (Watkin et al 2009). Barriers and cultural differences may influence the way different work cultures develop and the values that professionals hold about themselves and each other (Anning 2004).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Fourth, the perceived problems of professional tribalism, status/power differentials and resource shunting, identified in Table 3, are consistent with those identified as barriers to collaboration in other studies (see Rummery and Glendinning 1997). It was found that considerable time was needed to address these issues and explore ways that such cultural differences could be mitigated, a finding consistent with a recent study of an inter-professional learning programme in child protection (Watkin et al 2009). Barriers and cultural differences may influence the way different work cultures develop and the values that professionals hold about themselves and each other (Anning 2004).…”
Section: Discussionsupporting
confidence: 78%
“…Critical collaborative practice could address the problem of power and status differentials which are notoriously difficult to resolve and can all too easily undermine collaboration (Atwal and Caldwell 2005). In addition, many students mentioned the problem of having insufficient time to collaborate along with issues of trust, a finding consistent with other studies (Watkin et al 2009). Policy-makers were perceived as being motivated largely by the need to reduce costs and reinforce managerial imperatives, a finding that has emerged in other studies and further justifies the need for a critical approach to collaboration (see Huxley et al 2005;Saario and Stepney 2009;Stepney and Davis 2004).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar results were obtained by Ødegård [30] in a study of children's mental health care where employees used nearly half their working day on collaboration. It is clear that the development of good collaboration calls for time and discussions [12, 14, 25, 26, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…In earlier research, it has been shown that the detection of and early intervention in child maltreatment call for interprofessional collaboration [2, 9] to pool the knowledge, competencies, and resources of employees. In addition, separate agencies, workplace cultures and tasks require competence in interprofessional collaboration [1014]. Interprofessional services for children and families related to the detection of and intervention in child maltreatment are organized with different methods on both the national and international level.…”
Section: Introductionmentioning
confidence: 99%